POLÍTICAS E ESTRATÉGIAS DE REDUÇÃO DE DANOS PARA USUÁRIOS DE DROGAS - Jaime Alonso Caravaca Morera; Maria Itayra Coelho de Souza Padilha; Maria Terezinha Zeferino (Universidade Federal da Bahia, 2015)
<!--[if gte mso 9]> 0 0 1 144 823 Casa 6 1 966 14.0 <![endif]--> <!--[if gte mso 9]> Normal 0 false false false ES-TRAD JA X-NONE <![endif]--><!--[if gte mso 9]> <